Thực trạng tổ chức hoạt động trải nghiệm, hướng nghiệp cho học sinh ở một số trường trung học phổ thông tại thành phố Hà Nội - Âu , Thanh Ngọc; Hoàng, Thanh Thúy (Tạp chí Giáo dục, 2024)
Organizing experiential and career-oriented (ECO) activities for students is being implemented to meet the requirements of the 2018 general education program at high schools in Hanoi. The article discusses the current performance of content implementation and assessment in organizing experiential and career-oriented activities for high school students in Hanoi. The research results show that in the 4 content streams prescribed for organizing experiential and career-oriented activities, the groups of “self-oriented” and “career-oriented” content are implemented regularly and bring about effectiveness for students. In the evaluation stage, peer assessment, teacher assessment and learner self-assessment are the methods widely used in evaluating the process of organizing experiential and career-oriented activities for students. The results of this practical research will be the basis for developing measures to improve the quality of organizing experiential and career-oriented activities for high school students in Hanoi in the current educational context.